2011
DOI: 10.2215/cjn.06150710
|View full text |Cite
|
Sign up to set email alerts
|

Serum Fetuin-A Levels Are Associated with Vascular Calcifications and Predict Cardiovascular Events in Renal Transplant Recipients

Abstract: SummaryBackground and objectives Vascular calcifications predict cardiovascular disease, the major cause of death in renal transplant recipients (RTRs). We studied the determinants of fetuin-A, a potent circulating calcification inhibitor encoded by the AHSG gene, and tested its association with vascular calcifications and longterm survival and cardiovascular events (CVEs) in RTRs.Design, setting, participants, & measurements Two hundred seventy-seven prevalent RTRs from a single center were included. CVEs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 48 publications
(62 reference statements)
6
50
2
Order By: Relevance
“…It is plausible that inflammation and fetuin-A are factors in a shared pathophysiologic pathway, whereby chronic inflammation contributes to deficiency of fetuin-A, promoting dystrophic calcification and higher mortality risk (46). Lower fetuin-A levels have not been consistently associated with mortality or cardiovascular disease in populations not undergoing dialysis (16,(48)(49)(50)(51). In this study, we observed a threshold effect whereby only levels ,0.5 g/L were associated with increasing mortality, which may account for apparently conflicting results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is plausible that inflammation and fetuin-A are factors in a shared pathophysiologic pathway, whereby chronic inflammation contributes to deficiency of fetuin-A, promoting dystrophic calcification and higher mortality risk (46). Lower fetuin-A levels have not been consistently associated with mortality or cardiovascular disease in populations not undergoing dialysis (16,(48)(49)(50)(51). In this study, we observed a threshold effect whereby only levels ,0.5 g/L were associated with increasing mortality, which may account for apparently conflicting results.…”
Section: Discussionmentioning
confidence: 99%
“…OPG, OPN, and BMP-7 are produced by a variety of cell types, including endothelial and vascular smooth muscle cells, with increased expression in the setting of active calcification (12,14,15). Numerous clinical studies have demonstrated associations between these biomarkers and measures of vascular calcification and stiffness (16)(17)(18)(19)(20)(21)(22). In this study, we evaluated the association between selected calcification biomarkers and long-term mortality in a large, prospective cohort of incident dialysis patients.…”
Section: Introductionmentioning
confidence: 99%
“…All papers were observational studies: 11 were prospective, 10 analyzed the prevalence or progression of VC, and 3 studied the impact of VC and vascular outcomes. The prevalence of coronary artery calcification (CAC) in KTRs is higher (61-75%) than that assessed in stage 3 CKD [5,6,7] and lower than that found in hemodialysis patients [8], possibly due to a selection bias of KTRs upon admission to the waiting list. The determinants associated with its presence are: age, dialysis vintage, time on transplantation and high/low turnover bone disease [9].…”
Section: Cardiovascular Disease and Vascular Calcification In Kidney mentioning
confidence: 99%
“…Several studies carried out on dialysis patients and KTRs, as well as in the general population, have shown a strong association between a history of cardiovascular events and mortality with CAC [6]. Despite this, there is no clear indication for including non-contrast CT in the instrumental diagnostic procedure to detect the presence and entity of the calcium load and hence also subclinical atherosclerosis in kidney transplantation candidates and KTRs.…”
Section: Cac Assessmentmentioning
confidence: 99%
“…22 More recently, a direct link between decreased serum levels of Fetuin-A (a calcification inhibitor), aortic calcification, and CV outcome has been demonstrated in RTRs. 23 Increasing evidence supports the hypothesis that medial wall calcification is an important factor contributing to aortic stiffness, although studies comparing both calcification and stiffness in RTRs are not available. Calcineurin inhibitors, still a cornerstone in many immunosuppressive drug regimens, exert dose-dependent renal and systemic vasoconstrictive effects and may increase peripheral wave reflection.…”
Section: Verbeke Et Al Stiffness and Outcome In Renal Transplant Patimentioning
confidence: 99%